The relationship of self-efficacy and resilience with academic engagement: the mediating role of psychological hardiness - Fatemeh Yousefian (University of Hormozgan, 2023)
Objective: This study examines the interplay between self-efficacy, resilience, academic engagement, and the mediating role of psychological hardiness among a sample of 182 students at the Islamic Azad University of Bandar Abbas. Furthermore, the study explores the potential mediating role of psychological hardiness in this relationship. Methods: The research investigates the extent to which students' beliefs in their capabilities (self-efficacy) and their ability to adapt and rebound from challenges (resilience) relate to their active participation and involvement in academic activities (academic engagement). Data were collected through self-report questionnaires measuring self-efficacy, resilience, psychological hardiness, and academic engagement. Statistical analyses, including correlation and mediation analyses, were conducted to uncover the complex interactions among these variables. Results: The findings shed light on the pathways through which self-beliefs and psychological strengths influence students' academic engagement. Conclusions: This research contributes to our understanding of the psychological factors that impact students' academic experiences and outcomes.